Apology and Restitution in a Role-play Restorative Justice Experiment: Multiple Perspectives, Multiple Measures. Issue 2 (June 2020) - Kiefer, Rebecca P.; Worthington, Everett L.; Wenzel, Michael; Woodyatt, Lydia; Berry, Jack W.
Restorative justice provides an alternative to retributive justice by seeking to restore criminal offenders to be responsible members of the community. Often offenders will apologize (A) and offer to make restitution (R) for the damage done. Such offers might affect all parties present by promoting forgiveness (though that is not a stated goal of restorative justice), resolution of damages, and positive attitudes toward justice. We investigated Family Group Conferencing (FGC), which involves offender, victim, and supporters of each, in a mediated 30-minute dialogue. Namely, we organized role-play simulation meetings between "victims, " "offenders, " and the "mother" of each. There were 64 participants (16 groups of 4 participants). Each group role-played a mediated FGC that was video recorded. The offender had either to apologize and offer restitution (AR) or avoid both (No AR). Questionnaires assessed forgiveness (and other outcomes) from each of the four participants' perspectives. Coders coded behavior during the role-play. AR promoted forgiveness by all parties, but to different degrees. Coded "softness" of offender's behavior (i.e., nonverbal signs of remorse, contrition, and regret) affected victim's behaviors and ratings by women role-playing both mothers. The role-play simulation allowed some understanding of the inner working of FGCs relative to retrospective questionnaires.